Hypothyroidism New Aspects of an Old Disease - Kostoglou-Athanassiou, Ifigenia (IntechOpen, 2022)
Hypothyroidism is an endocrine disorder commonly caused by Hashimoto's disease. Nowadays, autoimmune diseases appear to be on the rise. As such, there is renewed interest in hypothyroidism. This book presents a comprehensive overview of the disorder with chapters on etiology and pathogenesis, precision medicine tools for detection, diagnosis and treatment, the morphology of the thyroid gland, the effect of hypothyroidism on various organ systems, and much more.